Life cycle assessment of industrial and urban wastewater treatment plant - Iwona Skoczko; Ewa Szatyłowicz; Magdalena Horysz; Łukasz Malinowski (Economic and Environmental Studies (E&ES), 2016)
Life Cycle Assessment (LCA) is a technique to assess environmental impacts associated with all the stages of a product's life from cradle to grave. With raising human population and the increasing industrialization, there has been very substantial increase in waste products too. Nowadays the importance of the wastewater treatment (domestic and industrial wastewater) need more attention in terms of the ecological balance. In this article a study was conducted and focused on the comprehension of the methods which are used for life cycle assessment and evaluation of environmental effects. In the proceeding sections of this study, Life Cycle Assessment method was used for evaluation the environmental advantages and expenses of other different wastewater treatment technologies and standards. An inventory of the input (chemical substances, electrical energy etc.) and output (emissions releases into the water, earth and the air, amount of sludge etc.) of the plants, where wastewater is treated, was documented. Potential environmental effects of the input and the output was assessed too. Finally, the obtained results were interpreted with regard to the objectives of LCA. With regard to these studies, attention was drawn to the importance of wastewater treatment plants which are regularly managed. Utilization of treatment systems resources and its effects on human health and ecology were assessed, finally the most suitable methods of wastewater treatment methods were tried to be explained with best examples.
Keywords: Q51; Q52; 330; Life Cycle Assessment; Wastewater Treatment; Wastewater Treatment Methods and Environmental Effects